PENGEMBANGAN E-MODUL BERBASIS DISCOVERY LEARNING PADA MATA PELAJARAN KONTROL REFRIGERASI DAN TATA UDARA KELAS XI TEKNIK PENDINGIN DAN TATA UDARA SMK NEGERI 1 PERCUT SEI TUAN - Saskia Rehani Br Tarigan; Nelson Sinaga (JEVTE Journal of Electrical Vocational Teacher Education, 2023)
Abstract This study aims to: (1) Find out how to develop an E-Module Based on the Discovery Learning Model for Refrigeration and Air Conditioning Control for students of SMK Negeri 1 Percut Sei Tuan. (2) Knowing the feasibility level of Discovery Learning Based E-Module which was developed for students of SMK Negeri 1 Percut Sei Tuan. (3) Knowing student responses to E-Modules Based on Discovery Learning Models in Class XI of Refrigeration and Air Conditioning Control subjects at SMK Negeri 1 Percut Sei Tuan. This research will be tested by involving class XI students of Refrigeration and Air Conditioning Engineering at SMK Negeri 1 Percut Sei Tuan in the odd semester of the 2022/2023 academic year. This type of research is Research and Development (R & D) with the ADDIE research model. The ADDIE research model includes 5 stages, namely first analysis which includes product needs analysis, second design, namely compiling outlines, layouts and E-Module material, third development, namely developing products that have been designed to be validated so that they get input from media experts and material experts, the fourth is implementation, namely implementing the product to get a response from users (students) to the E-Module that has been developed, the fifth evaluation, namely evaluating the E-Module based on some input from experts and user responses. The instruments used in this study were validation questionnaires and user response questionnaires. The results of this study are known: (1) This development research produces a product in the form of an E-Module Based on the Discovery Learning Model for Refrigeration and Air Conditioning Control. (2) The feasibility of this E-Module is obtained from the validation results of media experts in the "Very Eligible" category which obtains an average value of 3.4. And the results of the next validation were obtained from material experts in the "Very Eligible" category who obtained an average value of 3.4. (3) The results of user responses to this E-Module are categorized as "Very Good" which obtains an average score of 3.6 for students in small groups, 3.7 for students in large groups. The recommendation in this study is that the use of Discovery Learning Model-Based E-Modules in learning activities should be further developed in other subjects so as to increase student motivation and enthusiasm for learning.Â Key Words: Learning E-Modules, Discovery Learning, Refrigeration Control and Air ConditioningÂ AbstrakPenelitian ini bertujuan untuk: (1) Mengetahui cara mengembangkan E-Modul Berbasis Model Pembelajaran Discovery Learning Kontrol Refrigerasi dan Tata Udara untuk siswa SMK Negeri 1 Percut Sei Tuan. (2) Mengetahui tingkat kelayakan E-Modul Berbasis Discovery Learing yang dikembangkan untuk siswa SMK Negeri 1 Percut Sei Tuan. (3) Mengetahui respon siswa terhadap E-Modul Berbasis Model Pembelajaran Discovery Learning pada mata pelajaran Kontrol Refrigerasi dan Tata Udara Kelas XI di SMK Negeri 1 Percut Sei Tuan. Penelitian ini akan diuji coba dengan melibatkan siswa kelas XI Teknik Pendingin dan Tata udara SMK Negeri 1 Percut Sei Tuan semester ganjil tahun ajaran 2022/2023. Jenis penelitian ini adalah Research and Development (R & D) dengan model penelitian ADDIE. Model penelitian ADDIE meliputi 5 tahapan yaitu pertama analysis yang meliputi analisis kebutuhan produk, kedua design yaitu menyusun garis besar, layout dan materi E-Modul, ketiga development yaitu mengembangkan produk yang sudah didesain untuk dilakukan validasi agar mendapatkan masukan oleh ahli media dan ahli materi, keempat implementation yaitu menerapkan produk untuk mendapatkan respon dari pengguna (siswa) terhadap E-Modul yang telah dikembangkan, kelima evaluation yaitu mengevaluasi E- Modul berdasarkan beberapa masukkan dari para ahli serta respon pengguna. Instrumen yang digunakan pada penelitian ini adalah angket validasi dan angket respon pengguna. Hasil Penelitian ini diketahui : (1) Penelitian pengembangan ini menghasilkan produk berupa E- Modul Berbasis Model Pembelajran Discovery Learning Kontrol Refrigeradi dan Tata Udara. (2) Kelayakan E-Modul ini didapatkan dari hasil validasi ahli media dengan kategori â€œSangat Layakâ€ yang memperoleh nilai rata-rata sebesar 3,4. Dan hasil validasi berikutnya didapatkan dari ahli materi dengan kategori â€œSangat Layakâ€ yang memperoleh nilai rata- rata sebesar 3,4. (3) Hasil respon pengguna terhadap E- Modul ini dikategorikan â€œSangat Baikâ€ yang memperoleh nilai rata- rata sebesar 3,6 pada siswa dalam kelompok kecil, 3,7 pada siswa dalam kelompok besar. Rekomendasi pada penelitian ini adalah penggunaan E- Modul Berbasis Model Pembelajran Discovery Learning dalam kegiatan pembelajaran harus lebih dikembangkan lagi pada mata pelajaran lainnya sehingga dapat meningkatkan motivasi dan semangat belajar siswa..Kata Kunci: E-Modul Pembelajaran, Discovery Learning, Kontrol Refrigerasi dan Tata Udara